2001
DOI: 10.1073/pnas.101129698
|View full text |Cite
|
Sign up to set email alerts
|

Ubc9 interacts with a nuclear localization signal and mediates nuclear localization of the paired-like homeobox protein Vsx-1 independent of SUMO-1 modification

Abstract: Vsx-1 is a paired-like:CVC homeobox gene whose expression is linked to bipolar cell differentiation during zebrafish retinogenesis. We used a yeast two-hybrid screen to identify proteins interacting with Vsx-1 and isolated Ubc9, an enzyme that conjugates the small ubiquitin-like modifier SUMO-1. Despite its interaction with Ubc9, we show that Vsx-1 is not a substrate for SUMO-1 in COS-7 cells or in vitro. When a yeast two-hybrid assay is used, deletion analysis of the interacting domain on Vsx-1 shows that Ubc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 63 publications
2
57
2
3
Order By: Relevance
“…The sumoylation of certain key factor(s) such as PML might be crucial for the general mechanism of transcriptional control. Moreover, it was reported that UBC9 modulates transcription by ETS-1 and TEL independent of its enzymatic ability to conjugate them with SUMO-1 (59,60) and that UBC9 mediates the nuclear localization of Vsx-1 without its SUMO-1-conjugating activity (61). Thus, UBC9 may possess some other functions in addition to the role of a SUMO-1-conjugating enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The sumoylation of certain key factor(s) such as PML might be crucial for the general mechanism of transcriptional control. Moreover, it was reported that UBC9 modulates transcription by ETS-1 and TEL independent of its enzymatic ability to conjugate them with SUMO-1 (59,60) and that UBC9 mediates the nuclear localization of Vsx-1 without its SUMO-1-conjugating activity (61). Thus, UBC9 may possess some other functions in addition to the role of a SUMO-1-conjugating enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with their mammalian counterparts, zebrafish Ubc9.1 is changed at two amino acid residues, whereas Ubc9.2 is changed at one position, only (Kurtzman and Schechter, 2001). As a first step to explore the role of Ubc9 during zebrafish development, we analyzed the spatial and temporal expression patterns of the two ubc9 genes.…”
Section: Zebrafish Ubc9 Is Ubiquitously Expressed During Early Zebrafmentioning
confidence: 99%
“…Ubc9 is the human homolog of the E2 ubiquitin-conjugating enzymes of yeast that can transfer a ubiquitin-like molecule, called small ubiquitin-like modifier-1 (SUMO-1), to proteins in vertebrate cells (Desterro et al, 1997;Gong et al, 1997). However, Ubc9 also displays non-enzymatic effects on a variety of cellular actions (Hahn et al, 1997;Chakrabarti et al, 1999;Poukka et al, 1999;Kurtzman and Schechter, 2001) including GR-mediated transcription Cho et al, 2005). STAMP is a novel protein that was cloned by its ability to augment the modulatory activity of the coactivator TIF2 in both GR-mediated induction and GR-regulated repression of target genes .…”
Section: Introductionmentioning
confidence: 99%